An optimized nano-positioning stage for Bristol's Transverse Dynamic Force Microscope. Issue 21 (2016) - De Silva, G.; Burgess, S.C.; Hatano, T.; Khan, S.G.; Zhang, K.; Nguyen, T.; Herrmann, G.; Edwards, C.; Miles, M.
Abstract: This paper presents the design process for the optimisation of a nano-precision actuation stage for a Transverse Dynamic Force Microscope (TDFM). A TDFM is an advanced type of Atomic Force microscope (AFM) that does not contact the specimen and therefore has potential for increased accuracy and decreased damage to the specimen. The nano-precision stage actuates in a horizontal plane within a region of 1 μm×1μm and with a resolution of 0.3 nm. The non-contact TDFM has been developed at Bristol University for the precise topographical mapping of biological and non-biological specimens in ambient conditions. The design objective was to maximise positional accuracy during high speed actuation. This is achieved by minimising vibrations and distortion of the stage during actuation. Optimal performance was achieved through maximising out-of-plane stiffness through shape and material selection, as well optimisation of the anchoring system. The design was subject to constraints including an in-plane stiffness constraint, space constraints and design features relating to the laser interferometry position sensing system and subsequent controller design.